2020
DOI: 10.3390/geosciences10100417
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Anomaly and Model of the Lonar Meteorite Impact Crater in Maharashtra, India

Abstract: The ground magnetic field of the Lonar impact crater (Maharashtra State, India) and its surrounding area was measured and studied utilizing 2.5-dimensional potential field modelling. Field data showed the crater depression is associated with a strong circular negative anomaly with an amplitude of more than 1000 nT. The negative anomaly, however, decreases smoothly while moving from south to north. Most of the crater rim exhibits anomalous positive values. Negative anomalies at the rim are seen in the south - s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…The crater's depth was modelled to be about 500-600 m below the surface. In contrast, Kiik et al (2020) observed a negative magnetic anomaly over the crater and concluded that the post-impact brecciation and random distribution of clasts weaken the remanent magnetization compared to the surrounding Deccan basalts. Such a discrepancy in the magnetic model may arise from the complex nature of the breccia zone, which is largely unknown.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…The crater's depth was modelled to be about 500-600 m below the surface. In contrast, Kiik et al (2020) observed a negative magnetic anomaly over the crater and concluded that the post-impact brecciation and random distribution of clasts weaken the remanent magnetization compared to the surrounding Deccan basalts. Such a discrepancy in the magnetic model may arise from the complex nature of the breccia zone, which is largely unknown.…”
Section: Resultsmentioning
confidence: 94%
“…Using the first three drill holes, Fredriksson et al (1973) produced a depth cross-section showing a sedimentary layer with a maximum thickness of 100 m overlying a brecciated zone whose thickness exceeds 225 m. Later, Fudali et al (1980) concluded that four of the five drill holes did not actually reach the true bottom of the crater. Additionally, no consistent core-to-core correlation from all five drill holes was obtained, indicating that the exact extent of the brecciated zone is unknown (Fudali et al 1980;Kiik et al 2020).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…It provides a unique opportunity to study crater structures analogues to extraterrestrial craters on the bodies like Moon and the Mars [2][3][4] Despite a few attempts, the nature of the impactor is still not clear. The field survey shows the presence of maskelynite fragments and deformational features which confirm hypervelocity impact as the cause of the formation of Lonar crater [2,4,5]. Lakshmi and Kumar [4] have investigated impact and deduced that the impactor was of radius (R) 35m and density (ρ) 2900 kg/m 3 , with 20 km/s impact velocity (v).…”
Section: Introductionmentioning
confidence: 94%
“…The exercise is carried out with two target materials: basalt and bilayer of basalt and granite. The thickness of the basaltic lavas is taken as per known estimates of 500 m [5].…”
Section: Computational Detailsmentioning
confidence: 99%